Optimized Silicon Electrode Architecture, Interface, and Microgeometry for Next‐Generation Lithium‐Ion Batteries. Issue 1 (27th October 2015) - Molina Piper, Daniela; Evans, Tyler; Xu, Shanshan; Kim, Seul Cham; Han, Sang Sub; Liu, Ken Liang; Oh, Kyu Hwan; Yang, Ronggui; Lee, Se‐Hee
Abstract : Optimized performance of silicon‐ionic‐ liquid lithium‐ion batteries through the implementation of a new electrode‐microgeometry. The incorporation of 1D silicon nanowires into the cyclized‐polyacrylonitrile‐based electrode‐architecture allows for greatly improved active material utilization, higher rate capabilities, and reduced interfacial reactions.